2021
DOI: 10.1016/j.gocm.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Natural orifice transluminal endoscopic surgery in gynecology: What do we know till now?

Abstract: Surgical advancements are focusing currently on minimally invasive techniques, the latest of which is natural orifice transluminal endoscopic surgery. Though this approach is feasible through different natural orifices, the vaginal approach is the one which gained attention the most, given the vaginal flexibility and the ability to access pelvic and abdominal organs. Compared to gynecologists, general surgeons were precedents for using the vaginal orifice as a port of surgical entry. However, this vaginal appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…4 Following that, several studies have demonstrated that vNOTES can be performed successfully and safely in a series of gynecologic surgeries. [5][6][7] However, literature regarding vNOTES for ectopic pregnancy is still limited. Moreover, the techniques and equipment used vary considerably.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Following that, several studies have demonstrated that vNOTES can be performed successfully and safely in a series of gynecologic surgeries. [5][6][7] However, literature regarding vNOTES for ectopic pregnancy is still limited. Moreover, the techniques and equipment used vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the first case series of vNOTES in gynecology was published, and this series included four tubal ectopic pregnancies and one ovarian ectopic pregnancy 4 . Following that, several studies have demonstrated that vNOTES can be performed successfully and safely in a series of gynecologic surgeries 5–7 . However, literature regarding vNOTES for ectopic pregnancy is still limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Some articles have received wide attention and provide insight into the field of precision treatment for ovarian cancer 4 and natural orifice transluminal endoscopic surgery in gynaecology. 5 The accomplishment of these tasks would not have been possible without the dedication of our outstanding authors, reviewers and editors in the past years.…”
mentioning
confidence: 99%